Impact of social isolation during COVID-19 on psychological well-being of the elderly: an Indian survey-based study - Sharma, Rajni; Kumar, Krishan; Saini, Lokesh; Dhiman, Deepanshu; Ghai, Babita; Suri, Vikas; Singh, Subh Mohan; Mohendra, Ritin; Tyagi, Pooja; Prasad Barre, Vijay; Gupta, Nitin (International Journal Of Community Medicine And Public Health, 2021)
Background: Since the onset of COVID-19 pandemic the elderly population has started experiencing higher levels of anxiety both because of fear of contracting infection and due to restricted social life. Study was done to assess impact of lockdown on mental health of elderly. Methods: This was a retrospective and observational study. 106 participants were enrolled aged above 60 years. A Google survey form was sent to the participants for filling, accompanied by sessions with a clinical psychologist. The socio-demographic data and various psychological parameters were assessed. Results: Depression was most commonly reported (39.6%). Global satisfaction had a significant and positive correlation with both social security index (p=0.004) and social network scale (p=0.000). Conclusions: The prevalence of anxiety, stress and depression increased during lockdown. Overall satisfaction with life was reduced. Psychological counselling and support should be readily available to elderly. The problem associated with social isolation and lockdown may seem to be acute but can have worse psychological outcomes in long term.